Healthcare utilisation of pregnant women who experience sciatica, leg cramps and/or varicose veins: A cross-sectional survey of 1835 pregnant women. Issue 1 (February 2016) - Hall, Helen; Lauche, Romy; Adams, Jon; Steel, Amie; Broom, Alex; Sibbritt, David
Abstract: Background: Common discomforts of pregnancy experienced in the lower extremity include sciatica, leg cramps and varicose veins. Whilst research attention has focused on aetiology and outcomes, the health service utilisation of pregnant women suffering from these complaints has been largely overlooked. Aim: To examine the health status and health service utilisation profile of pregnant women experiencing sciatica, leg cramps or varicose veins. Methods: Linear and logistic regression was applied to a cross-sectional survey of a pregnant women drawn from the 1973 to 1978 cohort (aged 31–36 years in 2009), of the Australian Longitudinal Study on Women's Health ( n = 1835). Participant's demographics, health status and health service utilisation were compared for all three complaints based upon three subgroups (yes, sought help; yes, did not seek help; no). Findings: A number of women experienced sciatica (22.1%), leg cramps (18.2%) or varicose veins (9.4%). Of these, a greater proportion of women with sciatica (79.3%) or varicose veins (71.5%) sought help for their condition compared with women with leg cramps (46.7%). Comparisons between women with the conditions of interest who did seek help and those who did not only found that women with a university degree were 0.29 (95% CI: 0.10, 0.85) times less likely to seek help for their condition compared to women with a school only education. Conclusion: Further research examining all health seeking behaviour and treatment use of pregnant women who experience lower extremity problems is required in order to facilitate safe, effective and coordinated maternity care to further support these women during pregnancy.